2020
DOI: 10.3390/ani10101831
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Wheat Bran on the Morphology and Physiology of the Gastrointestinal Tract in Broiler Chickens

Abstract: There is increasing evidence showing that moderate amounts of insoluble dietary fiber can improve nutrient utilization by positively influencing the physiology of the gastrointestinal tract. The present study was conducted to investigate the effects of wheat bran as a source of insoluble fiber on nutrient digestibility, serum antioxidant status, gastrointestinal development, digestive enzyme activities and intestinal morphology in broiler chickens. A total of 96 one-day-old male Arbor Acre broiler chickens wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 45 publications
3
23
0
1
Order By: Relevance
“…Another study by Sadeghi et al [ 55 ] reported that supplementation of basal diet addition with rice hull (40 g/kg) and SBH (40 g/kg) could ameliorate adverse effects of coccidiosis on duodenal villus height but addition of only SBH in basal diet has positive response only on villus height to crypt depth ratio. Similarly, inclusion of wheat bran at a dose of 30 g/kg increased the villus height and villus height to crypt depth ratio [ 56 ].…”
Section: Effects Of Dietary Fiber On Nutrient Utilizationmentioning
confidence: 99%
“…Another study by Sadeghi et al [ 55 ] reported that supplementation of basal diet addition with rice hull (40 g/kg) and SBH (40 g/kg) could ameliorate adverse effects of coccidiosis on duodenal villus height but addition of only SBH in basal diet has positive response only on villus height to crypt depth ratio. Similarly, inclusion of wheat bran at a dose of 30 g/kg increased the villus height and villus height to crypt depth ratio [ 56 ].…”
Section: Effects Of Dietary Fiber On Nutrient Utilizationmentioning
confidence: 99%
“…It has been reported that additions of insoluble fibers at 1% in diets of pullets can increase the relative weights of proventriculus, gizzard and liver and improve pancreatic proteolytic activity [ 37 ]. Similarly, chickens fed 3% wheat bran have shown increased relative weights of gizzard, small intestine, and pancreatic amylase and trypsin activity that was correlated with increased nutrient digestibility [ 38 ]. The presence of such indigestible carbohydrates (i.e., cellulose, arabinoxylans) and other indigestible plant components (i.e., lignin) upregulate digestion activity as a means to compensate for the reduced hydrolysis of glycosidic bonds among molecules, resulting in an increased nutrient breakdown (digestibility) of others (i.e., starches, protein) [ 2 ].…”
Section: Effect Of Dietary Fiber In Poultry Dietsmentioning
confidence: 99%
“…Currently, one of the major challenges in poultry studies is to improve gut health by dietary modulation, especially during the early stages of life. dietary fiber has gained special attention due to its various beneficial effects on poultry (Shang et al, 2020). Increasing the structural components in the diet and manipulating the dietary fiber composition, has been shown to improve gut health, feed utilization and production efficiency and can alleviate enteric disease (Kheravii et al,2018).…”
Section: Introductionmentioning
confidence: 99%
“…Dietary non-starch polysaccharides (NSP), namely insoluble NSP, which have been shown beneficial effects on gut health, litter quality and nutrient utilization, by increasing crop and gizzard activity, stimulating digestive enzyme production and enhancing bacterial fermentation in the hind gut (Kheravii et al, 2018).There is increasing evidence showing that moderate amounts of insoluble dietary fiber can T improve nutrient utilization by positively influencing the physiology of the gastrointestinal tract (Shang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation